UTHM Cafe Food Ordering and QR Code Payment System for Efficient Cafe Management - Hannes Masandig; Azhari, Nur Adielah; Ainul Hisham, Ainul Aisyah; Noor Hisham, Iffah Amalia (Multidisciplinary Applied Research and Innovation, 2022)
UTHM Cafe Food Ordering System and QR Payment is a system that allows students at UTHM to order and buy food at the cafe. The payment method in this system is more convenient and effective of the fact that students can make payments using Online Banking and QR Payment payment methods. With this system, students can reduce their time to buy food in cafes and can reduce overcrowding in cafe. This is because, the problem often faced by students is that they have to be crowded when they want to buy food and student waited for a long queue while make payments, payments counters also have limited cash change is the most anticipated problems faced by the café owner. The UTHM Café system that we developed aims to facilitate and shorten the time students buy food and the payment system used in this system is very efficient in accordance with current payment methods. The methodology that has been used to develop this system is by using waterfall model. It has also been tested several times and got substaintial improvement good results. With this, it is hoped that this system can be developed and used for UTHM students, as well as know how to operate it.